Case report: Detection of non-O1/non-O139 Vibrio cholerae in a patient with hepatic space-occupying lesions using metagenomic next-generation sequencing - Zhang, Wei; Xiao, Li; Shan, Xingxing; Dai, Bing; Tang, Chunyan; Xian, Jianchun; Yu, Yan (Frontiers in Medicine, 2024)
Introduction/Background: Vibrio cholerae is the culprit of human intestinal infectious disease cholera, encompassing a variety of serogroup. However, there are relatively fewer reports of hepatic space-occupying lesions associated with this infection. At present, there are various detection methods for this pathogen, and metagenomic sequencing can detect the pathogen more quickly and accurately. In this report, metagenomic sequencing is employed to accurately identify non-O1/O139 Vibrio cholerae infections by analyzing the genetic material present in clinical samples. Presentation of case: A 75 year old male presented with diarrhea and fever following the consumption of crabs. Initial treatment resulted in improvement of the diarrhea; however, a liver abscess subsequently developed. Magnetic resonance imaging ( MRI) of the liver revealed hepatic space-occupying lesion. Upon further investigation, a gram-negative, rod-shaped bacterium was cultured from the patient’s liver puncture fluid. Additionally, Vibrio cholerae was detected in liver puncture fluid through metagenomic next-generation sequencing (mNGS). The pathogen was confirmed to be non O1/non O139 Vibrio cholerae (NOVC) by polymerase chain reaction (PCR). Following treatment with piperacillin/tazobactam sodium and moxifloxacin, the patient's body temperature normalized, the liver abscess showed significant improvement,, and he was subsequently discharged from the hospital. Discussion: This case involves an elderly male patient with hepatic space-occupying lesion. Multiple cultures of specimens failed to identify underlying the cause, but NOVC infection was conclusively identified through advanced techniques such as mNGS and PCR. Thus, it indicates that mNGS can serve as a valuable tool in cases of unexplained liver infection. Conclusion: The use of mNGS has great significance for the detection and clinical diagnosis of infectious pathogens in patients with unexplained space-occupying lesions.